THE REQUIREMENT OF EDUCABILITY (CIPEEX, 2024)
Based on a bibliographic research, this text aims to understand the requirement of humaneducability. In short, it is about shedding light to answer the question: “Why do we talk abouteducation and do we need it?”. In this sense, it is considered that the desire that this world candeepen and continue to exist, beyond the duration of a lifetime, feeds the desire to educatefuture generations. First, to get to know the human world and become familiar with it, it isnecessary to immerse oneself in the language, learn from others and incorporate the historicaland cultural legacy of previous generations. It is in this place that education is inserted, ameeting place between the old and the new. Thus, the need to preserve a heritage and takecare of those who come as a novelty is formed. If it has to do with those who arrived before usin this world, it fundamentally configures the educational field, since we always educate thegenerations that arrive from what represents our perceptions about the desirable – inheritedby the dialogue with the generations that preceded us – about the human and the human world,so that the generations understand our human condition. Taking responsibility for the commonworld and for the new generations is the essential task of all those who want the world tocontinue, last and deepen. This is, in our view, the crucial task of education, and it imposesthe requirement of educability!